Genetic variability and correlation studies of yield and phytic acid in F2 populations of maize (Zea mays L.) - A.S. Chandana; A. John Joel; R. Ravikesavan and; D. Uma (Electronic Journal of Plant Breeding, 2018)
A genetic study in the F2 populations of three crosses viz, UMI1200 x UMI1099, UMI1201 x UMI1099 and UMI1210 x UMI1099 was carried out in Kharif 2017. The genetic parameters studied include genotypic and phenotypic coefficient of variances, heritability, genetic advance as percent of mean and correlation coefficient. Performance of the individual genotypes of all the three F2 populations for 17 traits including seed yield and phytic acid revealed the presence of significant difference among genotypes, indicating the presence of genetic variability. Marginal difference between genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) indicated that variability was due to genetic factors for most of the traits studied. Traits that exhibited high heritability along with high genetic advance as percentage of mean (GAM) which can be used for selection were identified. Association studies depicted that plant height, cob placement height, cob length, cob breadth, number of rows per cob, number of kernels per row, cob weight, hundred kernel weight and shelling percentage exhibited positive correlation with yield. Correlation between yield and phytic acid content was found to be non-significant in the current study which revealed that selection can be progressed in both directions independently and its possible to obtain inbreds with low phytic acid content and high yield in the later generations through effective breeding and selection strategies.